PEMERIKSAAN INDEKS KEMIRIPAN DARI SKRIPSI BERBAHASA INGGRIS DENGAN TURNITIN UNTUK INTEGRITAS AKADEMIK - Yuliani Kusuma Putri (Politeknik Negeri Jakarta, 2022)
This research focuses on examining the similariry index of English Bachelor’s theses using Turnitin. The research which focuses on students’ academic writing is aimed to calculate the average and median from similarity index percentage identified by Turnitin; to examine the main sources of the similarities; and to identify the forms of the similarities from the highest main source. This study uses quantitative approach with descriptive method. This study shows the average and median from similarity index are both below 30%; and the main sources of the similarities are mostly websites. The forms of the similarities from the highest main source are sentences and even full paragraphs. The similarities identified by Turnitin cannot be all determined as plagiarism, since Turnitin only finds sources from digital repository that look similar. Turnitin is useful for the first step to maintain academic integrity in writing scientific papers at an institution.